Evaluation of Geothermal Reservoir Characteristics Based on Pressure, Temperature, Spinner (PTS) Analysis and Gross Permeability Test - Citra Wahyuningrum Citra (LPPMP Universitas Bhayangkara Jakarta Raya, 2026)
Geothermal energy is an alternative energy source that is increasingly important in meeting global energy needs. Well Completion is carried out to obtain well characteristic data through a series of tests. This study analyzes well X in field Y qualitatively and quantitatively using the Pressure, Temperature, Spinner (PTS) and Pressure Fall Test methods. Based on the quicklook analysis of the PTS graph, a liquid level injection of 1200 GPM was identified at a depth of 628 m from the pressure data. The correlation of temperature and spinner data shows four feed zones, namely at depths of 1074–1095 m, 1170–1195 m, 1232–1234 m, and 2604–2611 m. The slope value of the spinner analysis results against the cable speed is 7.2. The average fluid flow rate in each feed zone is -1.27 m/s, -1.42 m/s, -1.35 m/s, and -2.27 m/s, respectively. The largest mass flow rate contribution comes from the first feed zone at 11.06 kg/s (42%), followed by the second feed zone at 8.08 kg/s (30%), the fourth feed zone at 5.78 kg/s (22%), and the third feed zone at 1.38 kg/s (6%). The estimated production capacity reaches 13.15 MWe. The average Injectivity Index value is 532.81 tons/hr/coal. The results of the Pressure Fall Test show a reservoir permeability of 763.43 mD and a skin factor of -24.69, indicating improvements in reservoir characteristics.